Neuroprotective Effects of Some Nutraceuticals against Manganese-Induced Parkinson's Disease in Rats: Possible Modulatory Effects on TLR4/NLRP3/NF-κB, GSK-3β, Nrf2/HO-1, and Apoptotic Pathways - Karema Abu-Elfotuh; Ahmed Mohsen Elsaid Hamdan; Asmaa A. Mohammed; Ahmed M. Atwa; Magy R. Kozman; Amany M. Ibrahim; Shaimaa M. Motawea; Heba Mohammed Refat M. Selim; Sally Tohamy Kamal Tohamy; Mahmoud Nour El-Din; Sameh S. Zaghlool; Ayah M. H. Gowifel; et al. (MDPI AG, 2022)
Parkinson's disease (PD) is a progressive neurodegenerative disorder affecting the substantia nigra where functions controlling body movement take place. Manganese (Mn) overexposure is linked to a neurologic syndrome resembling PD. Sesamol, thymol, wheat grass (WG), and coenzyme Q10 (CoQ10) are potent antioxidants, anti-inflammatory, and anti-apoptotic nutraceuticals. We investigated the potential protective effects of these nutraceuticals alone or in combinations against MnCl2-induced PD in rats. Seven groups of adult male Sprague Dawley rats were categorized as follows: group (I) was the control, while groups 2-7 received MnCl2 either alone (Group II) or in conjunction with oral doses of sesamol (Group III), thymol (Group IV), CoQ10 (Group V), WG (Group VI), or their combination (Group VII). All rats were subjected to four behavioral tests (open-field, swimming, Y-maze, and catalepsy tests). Biochemical changes in brain levels of monoamines, ACHE, BDNF, GSK-3β, GABA/glutamate, as well as oxidative stress, and apoptotic and neuroinflammatory biomarkers were evaluated, together with histopathological examinations of different brain regions. Mn increased catalepsy scores, while decreasing neuromuscular co-ordination, and locomotor and exploratory activity. It also impaired vigilance, spatial memory, and decision making. Most behavioral impairments induced by Mn were improved by sesamol, thymol, WG, or CoQ10, with prominent effect by sesamol and thymol. Notably, the combination group showed more pronounced improvements, which were confirmed by biochemical, molecular, as well as histopathological findings. Sesamol or thymol showed better protection against neuronal degeneration and some behavioral impairments induced by Mn than WG or CoQ10, partly via interplay between Nrf2/HO-1, TLR4/NLRP3/NF-κB, GSK-3β and Bax/Bcl2 pathways.